Erythrocytes from patients with ST-elevation myocardial infarction induce cardioprotection through the purinergic P2Y 13 receptor and nitric oxide signaling - Jiao, Tong; Collado, Aida; Mahdi, Ali; Jurga, Juliane; Tengbom, John; Saleh, Nawzad; Verouhis, Dinos; Böhm, Felix; Zhou, Zhichao; Yang, Jiangning; Pernow, John (Basic research in cardiology, 2022)
Red blood cells (RBCs) are suggested to play a role in cardiovascular regulation by exporting nitric oxide (NO) bioactivity and ATP under hypoxia. It remains unknown whether such beneficial effects of RBCs are protective in patients with acute myocardial infarction. We investigated whether RBCs from patients with ST-elevation myocardial infarction (STEMI) protect against myocardial ischemia-reperfusion injury and whether such effect involves NO and purinergic signaling in the RBCs. RBCs from patients with STEMI undergoing primary coronary intervention and healthy controls were administered to isolated rat hearts subjected to global ischemia and reperfusion. Compared to RBCs from healthy controls, RBCs from STEMI patients reduced myocardial infarct size (30 ± 12% RBC healthy vs. 11 ± 5% RBC STEMI patients, P < 0.001), improved recovery of left-ventricular developed pressure and dP/dt and reduced left-ventricular end-diastolic pressure in hearts subjected to ischemia-reperfusion. Inhibition of RBC NO synthase with L-NAME or soluble guanylyl cyclase (sGC) with ODQ, and inhibition of cardiac protein kinase G (PKG) abolished the cardioprotective effect. Furthermore, the non-selective purinergic P2 receptor antagonist PPADS but not the P1 receptor antagonist 8PT attenuated the cardioprotection induced by RBCs from STEMI patients. The P2Y receptor was expressed in RBCs and the cardioprotection was abolished by the P2Y receptor antagonist MRS2211. By contrast, perfusion with PPADS, L-NAME, or ODQ prior to RBCs administration failed to block the cardioprotection induced by RBCs from STEMI patients. Administration of RBCs from healthy subjects following pre-incubation with an ATP analog reduced infarct size from 20 ± 6 to 7 ± 2% (P < 0.001), and this effect was abolished by ODQ and MRS2211. This study demonstrates a novel function of RBCs in STEMI patients providing protection against myocardial ischemia-reperfusion injury through the P2Y receptor and the NO-sGC-PKG pathway.